A prognosis model for clear cell renal cell carcinoma based on four necroptosis-related genes - Qiu, Qiangmin; Li, Yanze; Zhang, Ye; Hou, Yanguang; Hu, Juncheng; Wang, Lei; Chen, Zhiyuan; Lei, Yourong; Du, Yang; Liu, Xiuheng (Frontiers in Medicine, 2022)
Necroptosis is a caspase-independence cell death, and plays a critical role in regulation of cancer development. Now, little is known about the role of necroptosis-related genes in ccRCC. In this study, a risk model for the prognostic features of necroptosis was constructed by COX regression analysis based on the TCGA database. According to the risk score, patients with ccRCC were divided into low-risk and high-risk groups. Then, the OS was calculated by using the Kaplan-Meier curve. Using ROC curves analyses prediction accuracy. According to different clinical variables, we performed stratified analyses. Meanwhile, the correlation between clinical variables and risk scores was assessed, and the necroptosis-related genes with differential expression were mainly enriched in positive regulation of intracellular transport and platinum resistance pathways. The prognostic signatures for OS on the basis of 4 necroptosis-related genes was constructed and showed that the survival time was markedly longer in low-risk groups compared to in high-risk groups (P < 0.001). The area of ROC curve for OS was 0.717, which meant that our model had excellent predictive accuracy. In conclusion, we built an independently model which predicts the prognosis of patients, and provides insight into the underlying biological mechanisms of ccRCC necroptosis.